The Church and Constitutional Reforms in Kenya, 1992-2002: A Retrospective-Historical Analysis - Kapinde, Stephen Asol (European Scientific Journal, ESJ, 2018)
Religious leaders have played a leading role in the struggle for constitutional reforms in Kenya since 1990s.Significantly, they have argued over time that the constitution is the covenant of the nation and the ‘moral placenta’ of any meaningful democratic governance. This article therefore sets out to examine the mid-wifery role of religious leaders in negotiating for constitutional reforms in an attempt at consolidating democratic gains achieved following the repeal of section 2A of the then constitution on 19th December, 1991. The article is alive to the fact that the struggle for constitutional change in Kenya was an ‘hybrid enterprise’ which empirically cannot be analyzed by a single actor, entity or factor since many groups whether religious or civil society contributed in their own way in fighting for civil liberties and human rights. Methodologically, this is a retrospectivehistorical analysis of the contribution of the Church in the wider debate of constitutional making process between 1992 and 2002. The central question being addressed is on how the Church played out its activism in the glamour for constitutional reforms. It sets out on the premise that their activism towards constitutional reforms was undergirded by reconstruction paradigm as articulated by African Theo-philosophers such as Jesse Ndwiga Mugambi. Reconstruction paradigm is a theological trajectory that builds on the Ezra- Nehemiah motif. The article relies on archival sources as well as seven indepth oral interviews with key informants.